Racial and Ethnic Diversity at an Urban University: Critical Insight from a Developmental Social Justice Perspective - Larry G. Martin; Regina O. Smith; Raji Swaminathan (Adult Education Research Conference, 2007)
This paper applies an integrated developmental social justice framework to an existing qualitative data set in order to inform organizational learning and training programs. We argue that this perspective challenges the unexamined and unconscious assumptions, beliefs, and values that inform the organizational behaviors of individuals, groups, and organizations within adult and higher education.